Estimating the volatility of asset pricing factors - Janis Becker; Christian Leschinski (Journal of Forecasting, 2021)
Models based on factors such as size or value are ubiquitous in asset pricing. Therefore, portfolio allocation and risk management require estimates of the volatility of these factors. While realized volatility has become a standard tool for liquid assets, this measure is difficult to obtain for asset pricing factors such as size and value that include smaller illiquid stocks that are not traded at a high frequency. Here, we provide a simple approach to estimate the volatility of these factors. The efficacy of this approach is demonstrated using Monte Carlo simulations and forecasts of the market volatility.
Keywords: 519; asset pricing; factor models; realized volatility; volatility forecasting